Telaah Rasm Pada Manuskrip Mushaf Al-Qur`An Kuno Di Kalimantan Barat: Perbandingan Pada Manuskrip Mushaf Al-Qur`an Sanggau, Mushaf Ismahayana Landak Dan Mushaf Standar Indonesia - Buhori, Buhori; Hakim, Abdul; Abdi, Efan Chairul (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2024)
This article discusses the characteristics of the manuscripts of the Al-Qur'an manuscripts from the Sanggau collection of the West Kalimantan Museum and the manuscripts of Ismahayana Landak as well as a comparison of the aspects of rasm contained in these two ancient manuscripts in West Kalimantan, in comparison with the rasm system contained in Indonesian Standard Mushaf. The research methode used was content analysis in the form of text analysis which was carried out by taking an inventory of these two ancient manuscripts. This study shows that the manuscripts of the Sanggau are still intact with a total of 23, 190 pages, the number of lines per page is 15-17, and the width of the text size per page is 0.4 cm. No paragraph and page numbering was found. The text uses Khat Naskhi in black ink. Meanwhile, Ismahayana's Mushaf was written on European paper with an incomplete physical condition. No start page or illumination. The total pages are 273 and 546. The number of lines per page is 15-16 pages. The length and width of the text on the right side is 6 cm, the top width is 3.5 cm, the left side is 2 cm and the bottom line is 3 cm. The Naskhi khat type is written in black ink. The Sanggau Mushaf Manuscript and the Ismahayana Manuscript are written with rasm imlâ'i. However, the use of rasm is not applied consistently. Because in some writing certain pronunciations also use the rasm utsmâni pattern